Modulação da fotossíntese por açúcares e deficiência hídrica em plantas de cana-de-açúcar - Lobo, Ana Karla Moreira (2013)
The sugarcane has worldwide importance for storing large amounts of sucrose in the stalk. However, its production is limited by negative regulation in photosynthetic rate modulated by the sugars accumulation in the stalk (decrease in sink strength) or by the accumulation in the leaves (negative feedback). Another factor responsible for the reduction in photosynthesis and sucrose accumulation in the culm is the water deficiency presence. The mechanisms involved in the reduction in sucrose production by accumulation of sugars and drought are not yet completely understood. The aim of this study was to evaluate the inhibition processes of photosynthesis and changes in the metabolism of sugars induced by sugars and water stress in sugarcane plants. Therefore, two studies were conducted with sugarcane plants with four months old. At first, it was applied exogenous sucrose solution (50 mM) in the expanded leaves of plants grown in greenhouse conditions, followed by experiments on dose and timedependent sucrose in leaf segments and finalized by experiment with application of exogenous sugars (50 mM sucrose, glucose and fructose) in the expanded leaves of plants grown in controlled environmental conditions (phytotron). In the second study, the plants were subjected to irrigation suspension for five days in two environmental conditions: a greenhouse with natural conditions of high temperature, high vapor pressure deficit and high photosynthetic photon flux density (severe stress) and the second in phytotron conditions (moderate stress). The exogenous sucrose application caused changes in the sugars metabolism [alteration in sugars levels and activities of invertase acid soluble (SAI) and neutral (NI), sucrose synthase (SuSy) and sucrose phosphate synthase (SPS)]. Sucrose caused a strong reduction in CO2 assimilation and parameters of the activity of photosystem II. When compared with glucose and fructose, the sucrose caused greater reduction in maximum photosynthesis, carboxylation efficiency of PEP (Vpmax) and maximum rate of regeneration of PEP (Vpr). Furthermore, sucrose caused strong inhibition of Rubisco activity, decrease in its state of activation and reduction in its concentration (expression), whereas the PEPcase activity in vitro was unchanged. Water deficit caused decreases in photosynthetic rates, leaf gas exchange and photochemical, suggesting stomatal and non-stomatal limitations of photosynthesis. Gas exchanges were more affected in greenhouse conditions compared to the controlled environment of phytotron. Drought treatment caused increases in the soluble sugars levels in the leaves only in natural environmental conditions and under controlled conditions this treatment led to increases in NI and SPS activities while the activities of SuSy and SPS sheets were not changed. The maximum photosynthesis was decreased following the decrease of Vpmax and Vpr that were associated with a decrease in the PEPcase and Rubisco activities and expressions. Considering the results, it is concluded that sucrose negatively modulates photosynthesis of sugarcane per exercise a regulation in the Rubisco expression and activity. This effect leads to a reduction in the rate of carboxylation in vivo PEPcase probably by an indirect mechanism via modulation of the enzyme. Moreover, drought negatively modulates photosynthesis by different mechanisms affecting the Rubisco and PEPcase expression and activities reflecting reduction in the rates of carboxylation of PEP. In both cases studied was not possible to elucidate the role of changes in the metabolism of sugars in the regulation of photosynthesis. Therefore, the present study did not elucidate as sucrose and/or hexoses modify the Rubisco expression and activity and drought alters the Rubisco and PEPcase expression and activity.